Sequestration of plant pyrrolizidine alkaloids by chrysomelid beetles and selective transfer into the defensive secretions - Rahier, Martine; Witte, Ludger; Ehmke, Adelheid; Hartmann, Thomas; Pasteels, Jacques M. (My University, 1991)
Oreina cacaliae and O. speciosissima (Coleoptera, Chrysomelidae) sequester in their elytral and pronotal defensive secretions pyrrolizidine alkaloids (PAs) as Noxides (PA N-oxides). The PA N-oxide patterns found in the beetles and their host plants were evaluated qualitatively and quantitatively by capillary gas chromatography/mass spectrometry (GC-MS). Of the three host plants Adenostyles alliariae (Asteraceae) is the exclusive source for PA N-oxide sequestration in the defensive secretions of the beetles. With the exception of O-acetylseneciphylline the N-oxides of all PAs of A. alliariae, i.e. senecionine, seneciphylline, spartioidine, integerrimine, platyphylline and neoplatyphylline were identified in the secretion. PA N-oxides typical of Senecio fuchsii (Asteraceae) were detected in the bodies of the beetles but not in their secretion. No PAs were found in the leaves of the third host plant, Petasites paradoxus (Asteraceae). The results suggest the existence of two distinctive storage compartments for PA N-oxides in the beetle: (1) the defensive secretion, containing specifically PA N-oxides acquired from A. alliariae; (2) the body of the beetle, sequestering additionally but less selectively PA N-oxides from other sources, e.g. S. fuchsii or monocrotaline N-oxide fed in the laboratory. The concentration of PA N-oxides in the defensive secretion is in the range of 0.1 to 0.3 mol/1, which is more than 2.5 orders of magnitude higher than that found in the body of the beetle. No significant differences exist in the ability of the two species of beetles to sequester PA N-oxides from A. alliariae, although O. speciosissima, but not O. cacaliae, produces autogenous cardenolides. A negative correlation seems to exist between the concentrations of plant-derived PA N-oxides andde novo synthesized cardenolides in the defensive secretion of O. speciosissima.
Keywords: pyrrolizidine alkaloid N-oxides; alkaloid sequestration; defensive secretion; host plant; Coleoptera; Chrysomelidae; Oreina; Asteraceae; Adenostyles alliariae; Senecio fuchsii; Petasites paradoxus